A preliminary report on new Ediacaran fossils from Iran. Issue 2 (3rd April 2018) - Vickers-Rich, Patricia; Soleimani, Sara; Farjandi, Farnoosh; Zand, Mehdi; Linnemann, Ulf; Hofmann, Mandy; Wilson, Siobhan A.; Cas, Raymond; Rich, Thomas H.
Abstract : Vickers-Rich, P., Soleimani, S., Farjandi, F., Zand, M., Linnemann, U., Hofmann, M., Wilson, S.A., Cas, R. &Rich, T.H. November, 2017. A preliminary report on new Ediacaran fossils from Iran. Alcheringa 42, 231–244. ISSN 0311-5518. Recent exploratory field mapping of marine sedimentary sequences in the Koushk Mine locality of the Bafq region in Central Iran, and on the northern slopes of the Elborz Mountains south of the Caspian Sea, has yielded large complex body and trace fossils of Neoproterozoic–early Cambrian age. The recovered specimens resemble the previously documented Precambrian discoidal form Persimedusites, and a the tubular morphotype Corumbella, which is a novel occurrence for Iran and otherwise only recorded before from Brazil and the western USA. Additional enigmatic traces can not yet be interpreted unequivocally, but suggest that future work may uncover more unusual Ediacaran fossils from various localities in Central Iran. Patricia Vickers - Rich* [ prich@swin.edu.au, pat.rich@monash.edu ], Faculty of Science, Swinburne University of Technology, Melbourne (Hawthorn), Victoria 3122, Australia; Sara Soleimani [ sara_soleimani@yahoo.com ], Palaeontology Department, Geological Survey of Iran, Tehran, Iran; Farnoosh Farjandi [ farnooshfarjandi@gmail.com ], Department of Geochemical Exploration, Geological Survey of Iran, Tehran, Iran; Mehdi Zand [ zand.mehdi.geo@gmail.com ], Geology Department, Bafq Mining Company, Koushk Mine, Yazd, Iran. Ulf Linnemann [ ulf.linnemann@senckenberg.de ], and Mandy Hofmann [ mandy.hofmann@senckenberg.de ], Senckenberg Naturhistorische Sammlungen, Dresden, Museum für Mineralogie und Geologie, Sektion Geochronologie, Koenigsbruecker Landstrasse 159, D - 01109, Dresden, Germany; Siobhan A. Wilson [ sasha.wilson@monash.edu ], School of Earth, Atmosphere and Environment, Monash University, Melbourne (Clayton), Victoria 3800, Australia; Raymond Cas [ ray.cas@monash.edu ], School of Earth, Atmosphere and Environment, Monash University, Melbourne (Clayton), Victoria 3800, Australia; Thomas H. Rich† [ trich@museum.vic.gov.au ], Museum Victoria, Exhibition Gardens, PO Box 666, Melbourne, Victoria, 3001 Australia. *Also affiliated with: School of Earth, Atmosphere and Environment, Monash University, Melbourne (Clayton), Victoria 3800, Australia; School of Environmental Sciences, Deakin University, Melbourne (Burwood), Victoria, Australia 3125; Palaeontology Department, Museum Victoria, Carlton Gardens, PO Box 666, Melbourne, Victoria 3001, Australia. †Also affiliated with: School of Earth, Atmosphere and Environment, Monash University, Melbourne (Clayton), Victoria 3800, Australia; Faculty of Science, Swinburne University of Science and Technology, Melbourne (Hawthorn), Victoria 3122, Australia.